PENDEKATAN BLUE OCEAN STRATEGI DALAM PERSAINGAN BISNIS (STUDI EMPIRIS : HIDAYATULLAH HERBAL CENTER) KOTA SEMARANG - Umi Nasikah; Fia Ismawati; Indrika Novita Sari; Nunuk Purwati; Ratih Pratiwi (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2022)
Currently the development of the world economy is characterized by the process of globalization towards the free market, including herbal medicines that enter from various countries without clear protection that causes business competition will become more intense, causing companies to look for effective and efficient forms of marketing to introduce and market their products. Di Indonesia thedevelopment of drugs has been getting faster, especially herbalmedicines l, one of the companies is Hidayatullah Center Herbal Shop (H2C) in Banyumanik, Semarang. Hidayatullah Center Herbal Store (H2C) in Banyumanik, Semarang is a company engaged in the sale of various herbal products such as honey, goat milk, habbatussauda, olive oil, zam-zam water and others located in Banyumanik, Semarang. The purpose of this research was to find out and analyze the application of the Blue Ocean Strategy method  to increase sales and marketing levels at the Hidayatullah Herbal Center (H2C) Herbal Store in Banyumanik Semarang.  This prenelitian uses qualitative research methods, where the data and information obtained are collected through interviews (interviews), observations, and documentation. Thisstudy shows comparisons in the application of Blue Ocean Strategy seen using the remove-reduce-enhance-create scheme, strategy canvas and blue ocean index where hidayatullah herbal store center (H2C) in Banyumanik, Semarang focuses more on eliminating rogue retailers, increasing and developing company productivity, creating a strong promotion.  Accurate that can reach the wider community so that it can increase company sales, create a company's personal website to be able to support product marketing, organize retailer management, tighten quality control.